A cut-off value of epicardial fat thickness for the prediction of large for gestational age foetuses - Aydın, Emine; Tanacan, Atakan; Bulut, Ayça Nazlı (Taylor and Francis Inc., 2021)
Estimation of foetal weight in the prenatal period is important in many respects. For this purpose, during different periods of pregnancy; mostly in the last trimester; many methods or formulas have been described, almost of them using ultrasound. Foetal epicardial adipose tissue has previously been described as a metabolic organ in studies. Foetal epicardial fat tissue thickness (EFT) measurement has been previously described in the literature and has been associated with metabolic conditions such as preeclampsia or gestational diabetes. The purpose of this study was to determine the strength and cut-off value of EFT measured by ultrasound in the second trimester in the prediction of large for gestational age (LGA) foetuses. Epicardial fat tissue thicknesses which were recorded during second trimester anomaly screening were evaluated retrospectively. Birth weights of the same cases were also obtained from the database and analysed with IBM SPSS Statistics for Windows Version 22.0 (IBM Corp., Armonk, NY, USA). LGA babies had thicker EFT measurements and we established a cut-off EFT value of 1.38 mm. Our results suggest that EFT thickness measured by ultrasound in the second trimester may be useful in predicting LGA foetuses.Impact statement What is already known on this subject? It is known that foetal epicardial fat tissue is an adipose tissue with metabolic functions. Previously the relationship between this tissue and prenatal complications; such as, preeclampsia, gestational diabetes and infant growth and development were investigated. We planned this study considering that a tissue with metabolic functions affecting foetal growth may also affect birth weight. What do the results of this study add? Foetal epicardial fat thickness measurement only once in the second trimester may predict the 90th percentile limit at birth which is considered as the LGA limit.
Keywords: Epicardial Fat Thickness; Foetal Weight; Large For Gestational Age